2006
DOI: 10.1071/sr05137
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of management on soil biota in Vertosols supporting the broadacre grains industry in northern Australia

Abstract: Abstract. The grain-producing regions of northern New South Wales and southern and central Queensland are characterised by cropping systems that are strongly dependent on stored soil moisture rather than in-crop rainfall, and tillage systems that are increasingly reliant on zero or minimum tillage. Crops are grown relatively infrequently and crop rotations are dominated by winter and summer grains (wheat [Triticum aestivum L.] and sorghum [Sorghum bicolor L. Moench], respectively), with smaller areas of grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 45 publications
(51 reference statements)
1
21
1
Order By: Relevance
“…Various studies have demonstrated the impact of bulk density on enzymatic activity, soil communities and crop growth [54][55][56]. Similar to our findings, Bell, et al [57] reported the impact of different soil managements on soil biota from Hermitage fallow trial. This study revealed a marginally higher total enzymatic activity for CTSR in comparison with CTSB (P = 0.06).…”
Section: Soil Enzymatic Activity Was Higher For Ct Compared With Nt Ssupporting
confidence: 81%
See 2 more Smart Citations
“…Various studies have demonstrated the impact of bulk density on enzymatic activity, soil communities and crop growth [54][55][56]. Similar to our findings, Bell, et al [57] reported the impact of different soil managements on soil biota from Hermitage fallow trial. This study revealed a marginally higher total enzymatic activity for CTSR in comparison with CTSB (P = 0.06).…”
Section: Soil Enzymatic Activity Was Higher For Ct Compared With Nt Ssupporting
confidence: 81%
“…The fluorescent probe binds to a complementary sequence that can therefore be detected using fluorescence microscopy. Nowadays, FISH is a widely used tool in several fields in microbiology including ecology, phylogenetics, and diagnostics [57]. For example, the presence of live bacteria was detected in root segments of Arabidopsis thaliana by CARD-FISH, which is a variation of FISH that improve its sensitivity through the use of horseradish peroxidase-labeled probes in combination with catalyzed deposition.…”
Section: Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that two-time chisel tillage could have mixed soil between depths while one-time tillage did not. FDA activity includes esterase, lipase and certain protease activities (Caldwell 2005 (Bell et al 2006). Our previous studies also used the FDA method for measuring TMA of Australian soils, which ranged from 0.52 to 1.52 µg mL -1 g -1 soil h -1 at 0-10 cm and from 0.27 to 0.73 µg mL -1 g -1 soil h -1 at 10-20 cm for a Calcisol soil, and from 0.6 to 0.8 µg mL -1 g -1 soil h -1 at 0-10 cm and from 0.3 to 0.5 µg mL -1 g -1 soil h -1 at 10-20 cm for a Vertisol soil (Liu et al 2016a,b This provides another contrast with previous results on uniform clays, and warrants further investigation into texture contrast soils.…”
Section: St Effects On Soil Tmamentioning
confidence: 99%
“…Both MBC and MBN are simple methods for assessing the anthropogenic and environmental impacts on soil quality (Sparling et al 1997). Soil type, soil management practices and climatic conditions are important determinants in controlling soil microbial biomass (Bell et al 2006;Campbell et al 1997;Van Gestel et al 1993). Within any region, the variability between the aforementioned controlling factors underlines the importance of an extensive database to be maintained and developed.…”
Section: Introductionmentioning
confidence: 99%